Organisational commitment, job satisfaction and intent to leave among nurses at a public hospital in Johannesburg, South Africa - Mothoa, Lerato (My University, 2016)
The state of public health service and delivery in public hospitals in South Africa is concerning. Allied to this, is the prevalence of nursing shortage experienced in public hospitals in the country. Nursing shortage is an outcome that results from various factors; one such factor is actual turnover, preceded by intent to leave. Intent to leave is a strong predictor of actual turnover. It has been found to be negatively correlated with organisational commitment and job satisfaction. Organisational commitment and job satisfaction stem from various work states such job demands and job resources. It is important to understand that all occupations have job demands that are to be met by the required and relevant job resources. Failure to meet job demands with job resources results in numerous negative employee and organisational implications. In the nursing sector for instance, employee implications were found to include undesirable work behaviours (such as intent to leave) exerted by nurses which ultimately affect the state of the healthcare service and healthcare delivery. The purpose of the current research was to investigate the nature of relationships that exist among organisational commitment, job satisfaction, demographic variables and intent to leave among nurses working at a public hospital in Johannesburg, South Africa. The research postulated three hypotheses that were tested and proven Hypothesis 1: Organisational commitment (O_C) statistically predicts intent to leave (I_T_L) among nurse working at a public hospital; Hypothesis 2: Job satisfaction (J_S) statistically predicts intent to leave (I_T_L) among nurses working at a public hospital; Hypothesis 3: Demographic variables can also statistically predict intent to leave (I_T_L) among nurses working at a public hospital. Furthermore, the research aimed to find the best predictive model of the data. Lastly, the research investigated the relative importance of each significant independent variable in predicting intent to leave. The research design was a correlational cross-sectional. The public hospital received 200 questionnaires, of which 136 questionnaires were returned, with only 112 usable questionnaires to be analysed. Due to this, there were 112 participants. The sample fell predominantly in the 26-35 and 36-45 age categories. On the data collection days, nurses working in different wards received approximately three hours to complete a selfadministered questionnaire. Participants provided informed consent to be part of the research. The questionnaire collected demographic information, the respondent’s organisational commitment level, job satisfaction level and intent to leave level. All the three hypotheses were statistically proven, as indicated by results of the multiple linear regression. O_C was a statistically significant predictor of I_T_L (p < .05) among nurses at a public hospital. J_S was a statistically significant predictor of I_T_L (p < .05) among nurses at a public hospital. Nursing_position (category) as a demographic variable was also a statistically significant predictor of I_T_L (p < .05) among nurses at a public hospital. Hierarchical regression found the best predictive model of the data; the final predictive model was Model 3, which explained 17.3% of the variance in intent to leave. Model 3 included organisational commitment, job satisfaction and nursing position (category). Model3 equation = 61.848 + 2.395Nursing_position (category) + -.170O_C + -.111J_S. Lastly, the dominance analysis technique was applied in order examine the relative importance of each independent variable, to understand the role of each independent variable, and to assess the additional contribution of each independent variable in predicting intent to leave. O_C was found to have the additional contribution in predicting intent to leave. The current research showed that organisational commitment and job satisfaction remain applicable when examining intent to leave in the organisational behaviour. Therefore, the research findings are consistent with what has been previously discovered in the mid-nineties. Numerous strategies and plans have been put forward to increase organisational commitment and job satisfaction experienced by employees in order to mitigate nursing shortage, and to respond to the state of healthcare delivery in public hospitals. The challenge remains to be to translate these strategies and plans into actions. As it stands currently, thi is the only way to respond meaningfully to the highlighted phenomenon.
A research report submitted in partial fulfillment of the requirements for the Degree of Masters by Coursework and Research Report in the field of Industrial Organisational Psychology in the faculty of Humanities, University of the Witwatersrand.
Keywords: Quality of work life; Satisfaction